Seed Dormancy Release and Germination Requirements of Cinnamomum migao, an Endangered and Rare Woody Plant in Southwest China - Chen, Jing-zhong; Huang, Xiao-long; Xiao, Xue-feng; Liu, Ji-ming; Liao, Xiao-feng; Sun, Qing-wen; Peng, Liang; Zhang, Lan (Frontiers in Plant Science, 2022)
Seeds of the endangered plant Cinnamomum migao are known to exhibit dormancy and low germination, which may influence its regeneration; however, these characteristics remain unexplored. This is the first study to examine the dormancy types and improve the germination percentage of C. migao seeds. We evaluated the seed structure and characteristics (embryo and endocarp) and the effects of endogenous inhibitors. Furthermore, we assessed the effects of light, stratification, variable temperature, and gibberellic acid 3 (GA3) on the dormancy of C. migao seeds. The embryo was well developed, and the endocarp showed adequate water permeability; no obvious mechanical hindrance to germination was identified. However, the endocarp and embryo contained phenols and other germination inhibitors. Furthermore, the seed extracts delayed the germination of cabbage and ryegrass seeds, which indicates the presence of endogenous inhibitors. These findings suggest that C. migao seeds exhibit physiological dormancy. Among the several dormancy-relieving measures, light and 15°C/20°C variable temperature did not affect germination. On the other hand, GA3 pretreatment and variable temperature stratification effectively relieved dormancy. GA3 pretreatment combined with the 15°C stratification treatment was most effective in rapidly releasing the C. migao seed dormancy. Our findings may facilitate the storage and conservation of this endangered plant, which is currently underrepresented in ex-situ collections.